Language Register in Dried Fish Preservation in Calatagan, Batangas, Philippines - Hernandez, Thessa A. (European Publisher, 2019)
There are varieties of languages, some of these varieties are categorized according to speaker’s class, geographical location, work, etc. Register is a variety of language that has three dimensions: tenor, field and mode. This study aims to collect the register of language in Fish Preservation in Calatagan, Batangas, Philippines. The researcher lived for two weeks with the natives in Calatagan, Batangas to collect words used, starting from the preparation of the fishermen on their fishing materials, catching fishes, process in fish preservation and selling the products to the market. Twenty five percent of the fish in the province came from Calatagan. “Kuyog” (Siganus canaliculatus or Lo canaliculatus) is the species of fish commonly used in the fish preservation process. The wife of the fisherman is in-charge in the fish preservation process and they also sell the dried fish in the market. The researcher gathered sixty-two (62) words used by the fishermen and fish vendors in the fish preservation process. The study found out that there are specific words used starting from the creation of the fish net and boat, catching of fish up to the process of fish preservation and fish selling. The researcher recommended to make more research in language register in different domains.